Reservoir ecological health assessment Methods: A systematic review - Esi Esuon Biney; Charles Gyamfi; Anthony Yaw Karikari; Deborah Darko (Ecological Indicators)
This systematic literature review examined comprehensive methods for assessing the aquatic ecological health of artificial water reservoirs covering studies conducted globally from 1998 to 2023. The study employed the Protocol, Search, Appraisal, List, Synthesis, Analysis, and Reporting (PSALSAR) Framework and the Population, Intervention, Comparison, Outcome, and Context (PICOC) framework to identify 61 relevant literature. The findings revealed the predominant use of statistics, biological and ecological indices, physicochemical contaminant analysis, and biological indicators in aquatic ecological health assessments. The SLR further identified several gaps, including the absence of a consistent framework for ecological health assessments, inadequate data on plankton community indices and the limited adoption of advanced techniques such as molecular analysis, all of which limit comparability across regions due to varying environmental contexts. Recommendations for future research include the development of more robust ecological health indicators and enhanced data integration techniques such as multimetric indices, functional trait-based indices, and resilience indicators that assess traditional metrics like water quality and biodiversity and incorporate measures of ecosystem function, services, resilience, and adaptive capacity. The SLR also recommended a comprehensive and integrated approach for future reservoir studies that combine physicochemical analyses, trophic state indices, species composition and diversity measurements, bioindicator assessments, statistical analyses, and physical habitat evaluations. Additionally, land-use assessments and advanced tools, such as molecular analyses and ecotoxicity bioassays, were proposed to enhance assessment accuracy.